2014
DOI: 10.1111/jawr.12175
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Sediment and Nutrient Loads in Four Western Lake Superior Streams

Abstract: Total suspended solids (TSS) and total phosphorus (TP) have been shown to be strongly correlated with turbidity in watersheds. High‐frequency in situ turbidity can provide estimates of these potential pollutants over a wide range of hydrologic conditions. Concentrations and loads were estimated in four western Lake Superior trout streams from 2005 to 2010 using regression models relating continuous turbidity data to grab sample measures of TSS and TP during differing flow regimes. TSS loads estimated using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Considering this, and the results from other western Lake Superior basin streams (e.g. Ruzycki, 2011Ruzycki, , 2014Detenbeck et al, 2003Detenbeck et al, , 2005Anderson et al, 2003), it appears to be more appropriate to use storm events to investigate the relationship of sediment related parameters to landscape/land use while base flow may be more appropriate for dissolved and physical parameters.…”
Section: Hydrologic Regimesmentioning
confidence: 93%
See 1 more Smart Citation
“…Considering this, and the results from other western Lake Superior basin streams (e.g. Ruzycki, 2011Ruzycki, , 2014Detenbeck et al, 2003Detenbeck et al, , 2005Anderson et al, 2003), it appears to be more appropriate to use storm events to investigate the relationship of sediment related parameters to landscape/land use while base flow may be more appropriate for dissolved and physical parameters.…”
Section: Hydrologic Regimesmentioning
confidence: 93%
“…Ruzycki et al (2011Ruzycki et al ( , 2014 investigated the effects of flow and hydrologic regime on sediment related parameters -TSS, T, and TP -in four streams that drained into either the St. Louis River Estuary or the western arm of Lake Superior within 10 km of the estuary. They found that sediment related parameters varied strongly with hydrologic regime and discharge and that there were significant differences between streams that were near each other.…”
Section: Hydrologic Regimesmentioning
confidence: 99%
“…A non-parametric or smearing estimator was first applied by Duan (1983) [34] in order to improve SRC estimation. This method is used for solving SRC limitation by [35][36]37]. Ferguson (1986) [32] used a quasi-maximum likelihood estimator (QMLE) to correct the shortcomings of the basic SRC method.…”
Section: Introductionmentioning
confidence: 99%
“…Relationships have been documented between turbidity and many pollutants, including total nitrogen (Kim and Furumai 2013), particulate organic nitrogen and carbon (Slaets et al 2014), total phosphorus and total suspended solids (TSS) (Jones et al 2011;Ruzycki et al 2014), mercury (Ruzycki et al 2011), polycyclic aromatic hydrocarbons (PAHs) (Rügner et al 2014), pathogens (USEPA 1999;LeChevallier and Norton 1992;Brookes et al 2005;Johnson et al 2010), and various indices of aquatic habitat quality (Lloyd 1987;Kirk 1991;Henley et al 2000;Bilotta and Brazier 2008;Hazelton and Grossman 2009). Besides water quality and aquatic habitat, turbidity has been often reported as an indicator of surface water's aesthetic appearances.…”
Section: Introductionmentioning
confidence: 99%
“…Turbidity has been used to estimate SSC (Rügner et al 2013;Ruzycki et al 2014). Parmelee and Ellms (1899) used measured turbidity to estimate SSC using a platinum and copper wire as an indicator of turbidity.…”
Section: Introductionmentioning
confidence: 99%